Legal and Religious Controversies in Eliminating Female Khitan (Circumcision) - Al Fahrezi, Ahmad Fikri; Muhibbussabry (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: The Indonesian Government Regulation No. 28/2024, particularly Article 102, has sparked national debate due to its prohibition of female circumcision—a practice that remains prevalent in several Muslim communities. While global health institutions classify it as female genital mutilation (FGM), many Islamic scholars continue to defend it as a religiously mandated act. Purpose: This study aims to explore the responses of local religious leaders to this policy change, with a particular focus on how legal, theological, and cultural arguments shape their resistance or acceptance. Methods: A qualitative method with a normative juridical approach was employed. Data were collected through semi-structured interviews with four prominent religious leaders in Pamatang Simalungun Village, complemented by document analysis of fatwas and official religious statements. Thematic analysis was used to identify key discourses and legal-religious justifications. Results: The findings reveal a strong resistance among religious leaders, primarily based on classical Shafi’i jurisprudence that considers female circumcision mandatory. Participants argued that the policy undermines religious authority and fails to accommodate socio-cultural contexts. Health risks were downplayed in favor of scriptural interpretations. Implication: The study demonstrates a significant epistemological gap between public health policy and religious reasoning. Originality: A more dialogical policy model that incorporates religious leaders into the legislative process to bridge legal legitimacy and religious compliance.